Publication ethics and scientific misconduct - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
To maintain the readers' trust and to uphold the journal's reputation, it is paramount for the entire research, peer reviewer and publication process to follow ethical principles and decisions. Studies involving humans, animals, medical records and human tissues/organs need to be conducted ethically, and the appropriate approvals obtained. The privacy and confidentiality of patients, authors and reviewers should be respected. When required, rights and permissions should be sought. Common forms of scientific misconduct include misappropriation of ideas, violation of generally accepted research practices, failure to comply with legislative and regulatory requirements, falsification of data, and inappropriate behaviour in relation to misconduct. Authors can expect editorial action to be taken, should duplicate publication, plagiarism and other forms of scientific misconduct be attempted or detected.